RECONCEPTUALIZING TEFL MATERIALS: A CRITICAL REVIEW OF DECOLONIAL, CULTURAL, AND ECOLOGICAL PERSPECTIVES - Sutarmo; Kalayo Hasibuan; Faurina Anastasia; Chandra Alfindodes (JEE (Journal of English Education), 2026)
Teaching English as a Foreign Language (TEFL) materials are increasingly viewed not only as pedagogical tools but also as ideological, cultural, and ecological artifacts that shape learners’ understanding of language, identity, knowledge, and society. Despite this growing awareness, many EFL materials continue to privilege Western epistemologies, marginalize local knowledge systems, and provide limited attention to ecological concerns. This critical literature review synthesizes studies published between 2000 and 2025, with particular emphasis on recent scholarship from 2021–2025, to examine how decolonial, cultural, and ecological perspectives have been represented in TEFL materials research. Using thematic narrative synthesis, the review identifies several recurring themes: the persistence of Western-centered representation, uneven integration of local cultural knowledge, limited incorporation of ecological perspectives, and the emerging influence of digital and AI-mediated materials. Unlike previous studies that discuss these perspectives separately, this review integrates them into a unified framework grounded in epistemic justice, contextual relevance, and sustainability awareness. The study contributes a conceptual framework for transformative materials development and highlights implications for textbook design, teacher education, and future research, particularly in Global South contexts.